Reinterpreting Religious Texts on Gender Equality: The Perspective of Ahmad Syafii Maarif - Rizal, Deri; Irman, Irman; Putri, Dewi; Miftahurrahmah, Miftahurrahmah; Yustiloviani, Yustiloviani; Kamaluddin, Kamaluddin (JURIS (Jurnal Ilmiah Syariah), 2024)
This study examines Ahmad Syafii Maarif’s (commonly known as Buya Syafii Maarif) views on gender equality, highlighting the distinctive aspects of his interpretation of religious texts, particularly regarding family and societal roles. Using a descriptive-critical methodology, the study reveals that Buya Syafii Maarif’s views on gender equality within the family emphasize justice, fairness, and respect for women’s rights, all rooted in Islamic principles. He argues that a correct interpretation of Islam supports equality between men and women, including within family relationships. A central aspect of his thinking is the concept of complementary roles between men and women, rejecting the idea of gender-based superiority. He critiques traditional views that confine women’s roles to the domestic sphere and advocates for greater female participation in decision-making and social contributions. Buya Syafii Maarif also challenges interpretations of religious texts that have historically justified gender inequality, asserting that the Qur’an promotes respect and cooperation between the genders. Education plays a key role in his vision, as he emphasizes its transformative power in empowering women to make significant contributions to both family and society. He advocates for equal opportunities for women in education and public life to foster a just and prosperous society. This study demonstrates that Buya Syafii Maarif's vision of gender equality reflects a balanced and just understanding of Islam, one that encourages cooperation and equality to achieve harmony in both the family and society.